Lateral interactions and azimuthal orientation of pure and coadsorbed benzene layers on Ni(111) - Huber, W.; Zebisch, P.; Bornemann, T.; Steinrück, Hans-Peter (Surface Science, 1991)
The adsorption of benzene and the coadsorption of benzene with electronegative coadsorbates on Ni(111) have been studied by angle-resolved UPS using linearly polarized synchrotron radiation. The electronic structure of benzene coadsorbed with NO, CO and O in the ordered (2 3×2 3)R30° layers and for the coadsorbed (3 × 3) benzene + NO layer is similar to that of pure benzene layers. Uniform shifts of the various benzene levels to lower binding energy (0.2-0.3 eV) in the coadsorbed layers are attributed to electrostatic initial state effects. In all pure and coadsorbed layers studied, the benzene molecules are oriented with their molecular plane parallel to the surface with the molecular symmetry reduced to C . In the nonsaturated benzene layer and in the coadsorbed layers with (2 3×2 3)R30° structure the molecules are azimuthally oriented with the hydrogens pointing along the [211] directions of the substrate. In the saturated pure ( 7× 7)R19.1° layer and the (3 × 3) benzene + NO layer the molecules are azimuthally reorientated due to lateral interactions. The proposed azimuthal reorientations are in agreement with expectations from steric arguments. For the saturated pure ( 7× 7)R19.1° layer the 2a levels exhibits a dispersion of 0.45 eV. also indicative of lateral interactions. © 1991.